Prototype Development Model Application Visualization Jarimatika Simple and Interest Based Website for Early Childhood Education - Maria Atik Sunarti Ekowati; Darsini Darsini (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
A process that produces prototype called prototyping. Prototype development steps: identify, develop, define Prototype accepted, use, coding, testing, determine the system that has received the user, use. The study was conducted on children in kindergarten and early childhood Dikspora Surakarta Regional Office, 2014 and 2015, financed Higher Education, and has produced a model of visualization applications Jarimatika simple as a refinement of research conducted in 2012 in SD Canisius Semanggi, Surakarta. The purpose of research is to develop a model visualization Jarimatika with WEB-based model design. The process of learning mathematics in schools was introduced through a WEB-based Jarimatika method. And through the website are expected to Prototype Development Model Application Visualization Jarimatika Simple and Interest Based WebSite For Early Childhood Education, translate into something useful for the development of the nation, as the future generation. From the research results can be seen that the technique Jarimatika is very important for the study of mathematics, especially early childhood, therefore, the development of prototype model of application visalisasiJarimatika is a solution that can help children to learn mathematics, and bring in the website is part of the technology development appropriate, so that parents can specifically learn through your online media on the internet, and not just parents student of 20 samples in the region of Surakarta official who can learn but all those who want browshing and willing to learn Jarimatika through internet media online. Basic application development using Macromedia Flash Professional 8 Portable Version, a programming language Action Script and XML database, the design view wear Makromedia flash Prof 8 and adophe firework, phpMyAdmin database design and Sequel Pro and output Prototype Model Visualization Jarimatika.Keywords: Prototype, Model, Visualization, Jarimatika, Website